Proses Memori Konsumen di Era Digital: Tiktok, Fuji dan Pembentukan Preferensi Pangan Gen Z: Studi Kasus Konten Snack Tray Haus - Iga Trisna Purnama Dewi Ningrat; Prima Mulyasari Agustini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In today's digital era, which emphasizes visual engagement and social participation, social media platforms such as TikTok have emerged as key mediums for shaping perception, memory, and consumption preferences among younger generations, particularly Generation Z. This study aims to analyze the mechanism of consumer memory in forming food preferences for the product snack tray Haus!, mediated through content created by influencer Fujianti Utami (Fuji) on TikTok. Employing a descriptive qualitative approach with a case study method, data were collected through content observation, online surveys with 16 Gen Z respondents, and triangulated with insights from internal representatives of HAUS! Indonesia. The findings reveal that Fuji’s visual content successfully activates consumer memory in alignment with the three-stage memory model proposed by Michael R. Solomon (2019): sensory memory, short-term memory, and long-term memory. The visual and emotional stimuli in the content facilitate encoding processes and strengthen brand association in the consumer’s mind. Repetitive exposure and TikTok’s algorithmic support enhance long-term memory retention even without direct consumption experience. Influencers also function as emotional and social mediators, signaling strong behavioral cues to Gen Z consumers, especially through the Fear of Missing Out (FOMO) effect. The study concludes that digital consumption preferences are shaped through a combination of visual cognition, digital affection, and authentic communication strategies.